Islamic Book Publisher In Medan; Challenge In Digital Era - Saidatul Khairiyah (Proceeding International Seminar of Islamic Studies, 2019)
Publishing is one of three aspects in transmission link of knowledge. The role of publisher is highly significant in expanding knowledge. Reviewing the history of Medan that ever been a book publishing center in Indonesia. Book publishers appeared, some even have popular name such as Madju, Hasmar and Islamiyah. The publishers published books from all branches of knowledge. Entering the 2000s, the publishing world suffered a setback, some even went out of business, the rests survived such as Madju but only to carry out their function as printing house. The high cost of production, the high price of paper, government policies, and piracy have become the causes. The emersion of ebook as product of digital era has offered solutions of sluggishness in publishing world. However, the publishers readiness is needed to meet this challenge.